"We thought it would be easy": recruitment challenges, successes and best practices for low-income couple populations. Issue 3 (3rd April 2019) - Roberts, Kelly M.; Patterson, Jennifer L.; Burr, Brandon K.; Jefferson, Sean; Hubler, Daniel S.
Abstract: Recruitment challenges present ongoing struggles for social science professionals. Especially problematic are recruiting endeavors when target populations are highly stressed, highly mobile, and are comprised of couples rather than individuals. Included in this study is a rationale supporting the need to study recruitment challenges coupled with a literature review discussing recent recruitment research summaries. Based upon a Delphi-type discussion with couples relationship education (CRE) experts, our team constructed a qualitative study to examine recruitment challenges in low-income CRE programs. Fourteen interviews were conducted with "successful" program leaders identified by federal regional managers within the Administration for Children and Families (ACF). Data were analyzed, and results detailing four main "challenge" themes, four "success" themes, and a seven-step best practice model are presented.